PERAN FILSAFAT ILMU DALAM PENDIDIKAN IPS - Winda Cicilia; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The Philosophy of Social Studies Education is not much different from other philosophies of educational sciences, because the philosophy of Social Studies Education is also an educational philosophy that discusses the actions of social science education aimed at making individuals or students able to understand social problems and be able to overcome them and be able to make the right decisions about the problems faced in their lives. The method used in this study is Literature Review. The role of educational philosophy can provide thoughts or ideas, namely stating educational goals for citizens, providing appropriate and clear instructions by asking questions about educational regulations and practices in the outdoor environment using clues from the ideas / concepts of educators.